Antropomorficzna szlufka z okolic Międzyrzecza. Z badań nad kulturą materialną późnośredniowiecznych mieszkańców pogranicza wielkopolsko-brandenbursko-śląskiego = An anthropomorphic belt loop from Międzyrzecz surroundings. From research on the material culture of late medieval inhabitants of the greater Poland-Brandenburg-Silesian borderland - Janowski, Andrzej; Michalak, Arkadiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The text presents a find of a decorative belt loop recovered in the area of Międzyrzecz. The find measuring: height 69,7 mm, width 27 mm, thickness 3-5 mm and it depicts a male figure in a short outfit with a hood and in tight trousers.
Keywords: Międzyrzecz; średniowiecze; moda; pas; 15-16 w.; Middle Ages; fashion; part of the belt